Optimizing Stock Returns Portfolio Using the Dependence Structure Between Capital Asset Pricing Models: A Vine Copula-Based Approach - Autchariyapanitkul K. (2017)
© Springer International Publishing Switzerland 2016. We applied the vine copulas, which can measure the dependence structure of uncertainty in portfolio investments. C-vine and D-vine copulas based on capital asset pricing models were used to exhibit portfolio risk structure in the content of asset allocation. With this approach, we employed the Monte Carlo simulation and the empirical results of C-vine and D-vine copulas to determine the expected shortfall of an optimally weighted portfolio. Furthermore, we used the condition Value-at-Risk (CVaR) model with the assumption of C-vine and D-vine joint distribution to gain the maximum returns in portfolios.